The Relationship between Parental Support and Children's Future Orientation in Koto Tangah District - Vadila Putri, Vici; Sunarti, Vevi (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
The background for conducting this research is because of the high number of teenagers dropping out of school in Koto Tangah District. The research objectives were to 1) describe parental support for children in Koto Tangah District, 2) describe children's future orientation in Koto Tangah District, and 3) determine the relationship between parental support and children's future orientation in Koto Tangah District. This research includes quantitative correlational research. The population in this study were all mothers of school dropout children in Koto Tangah District, totaling 30 people. Total Sampling Technique is a technique for taking as many samples as the population. Researchers determined the research sample to be 100% of the population. The data collection technique is a questionnaire, the data collection tool uses a questionnaire which contains a list of statements or questions. Data analysis techniques are percentages and the Spearman Ro correlation formula. The research results show that (1) parental support for children in Koto Tangah District is categorized as very supportive of children's education, (2) the future orientation of children's education in Koto Tangah District is still classified as high future orientation, and (3) there is a significant relationship significant relationship between parental support and children's future orientation in Koto Tangah District.Keywords: parental support, future